Analysis of ROH patterns in the Noriker horse breed reveals signatures of selection for coat color and body size. (14th June 2019) - Grilz‐Seger, G.; Druml, T.; Neuditschko, M.; Mesarič, M.; Cotman, M.; Brem, G.
Summary: Overlapping runs of homozygosity (ROH islands) shared by the majority of a population are hypothesized to be the result of selection around a target locus. In this study we investigated the impact of selection for coat color within the Noriker horse on autozygosity and ROH patterns. We analyzed overlapping homozygous regions (ROH islands) for gene content in fragments shared by more than 50% of horses. Long‐term assortative mating of chestnut horses and the small effective population size of leopard spotted and tobiano horses resulted in higher mean genome‐wide ROH coverage ( S ROH ) within the range of 237.4–284.2 Mb, whereas for bay, black and roan horses, where rotation mating is commonly applied, lower autozygosity ( S ROH from 176.4–180.0 Mb) was determined. We identified seven common ROH islands considering all Noriker horses from our dataset. Specific islands were documented for chestnut, leopard spotted, roan and bay horses. The ROH islands contained, among others, genes associated with body size ( ZFAT, LASP1 and LCORL/NCAPG ), coat color ( MC1R in chestnut and the factor PATN1 in leopard spotted horses) and morphogenesis ( HOXB cluster in all color strains except leopard spotted horses). This study demonstrates that within a closed population sharing the same founders and ancestors, selection on a single phenotypic trait, in this case coat color, can result in genetic fragmentation affecting levels of autozygosity and distribution of ROH islands and enclosed gene content.